Microrna-206 induces hypoxic necrosis of femoral head by inhibiting VEGF/PI3K/AKT signaling pathway - Wu, Xingjing; Tao, Zhoushan; Cheng, Wenjing (Frontiers in Genetics, 2023)
The most common form of nontraumatic necrosis of the femoral head is anoxic necrosis of the femoral head, which is a metabolic disease, mainly involving young and middle-aged people. Bilateral onset is more than unilateral, with a wide range of necrosis. In recent years, the chemotherapy drug delivery system is very effective in the treatment of femoral head necrosis. Anoxic necrosis of the femoral head is a pathological process of osteonecrosis caused by inappropriate use of steroids. Apoptosis and its related signal regulation pathway play an important role in the occurrence and development of hypoxic necrosis of the femoral head. In order to investigate the possible pathological manifestations of miR-206 and VEGF/PI3K/AKT signal pathway genes and their interactions in hypoxic necrosis of the femoral head, this paper intended to systematically study the expression and regulation mechanism of miR-206 and VEGF/PI3K/AKT signal pathway genes. The interaction between miR-206 and VEGF/PI3K/AKT signaling pathway and its regulation on apoptosis, differentiation and proliferation of human osteoblast cell line hFOB1.19 (SV40 transfer of human osteoblasts) were studied by double luciferase reporter gene analysis, overexpression and inhibition of miR-206, and gene silencing of VEGF/PI3K/AKT signaling pathway. After 24 hours and 48 hours of intervention with MicroRNA 206 on osteoblasts, it was found that the fluorescence intensity of caspase-3 was higher than that of 0 hour group (P<0.05). This paper has provided an important research basis for the research of femoral head necrosis and the development of new diagnosis and therapeutic drugs for this kind of disease. It also has provided a reference for the further promotion of the chemotherapy drug delivery system.